Integrating Translation Technology in the Specialised Translation Classroom to Contextualise Learning - Plaza-Lara, Cristina (My University, 2017)
Recent approaches to translation training have emphasized the need to include in the classroom a real working context and to promote situational learning (cf. Kelly, 2005: 16-18 ). For the specialised translator, new technologies and, consequentially, the instrumental-professional sub-competence, have become as important as linguistic-cultural knowledge. For this reason, in this contribution, a didactic proposal will be presented to incorporate new technologies (computer-assisted translation and localisation tools) in the scientific/technical translation classroom, as well as a proposal to coordinate different subjects in the curriculum to promote horizontality in contents. Modality and type of translation are not mutually exclusive. For this reason, the main objective of this contribution is to merge both concepts with a learning proposal in which new technologies become another essential working tool in the specialised translation classroom. Nowadays, the meaning of localisation goes beyond the translation of software, video games and websites and it has caused important changes in the translation process and the translation industry. In Spain, it is compulsory to include in the Translation and Interpreting curriculum subjects such as documentation, terminology and computer science. These subjects are normally offered in the first years of the degree, when students have only basic knowledge of translation. If these skills are not put into practice in later years of the degree, students will not understand the operating principles of these tools. In this regard, it is essential that the different subjects in the curriculum are coordinated to ensure learning contextualisation and the employability of future graduates. Different activities directly related to computer-assisted translation and localisation will thus be presented in order to integrate and improve the knowledge acquired in previous years and new skills regarding specialised translation.
Keywords: Traducción; Computer-assisted translation; Localisation; Scientific/technical translation; Instrumental-professional competences; Horizontality in curriculum